The Determination Selling Price of Opium Koffie Businesses in Lemahabang Area - Fadilah Muhamad; Rini Marlita; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Formosa Journal of Science and Technology, 2023)
The aims of this visit is to understand the pricing determination used by Candu Koffie Business in Lemahabang. The visit method used is the description and observation method, which aims to explain the company's condition based on existing facts and information obtained to acquire knowledge and draw conclusions about the current situation. The type of data used is primary data sources through direct interviews with the business owner and documents. Candu Koffie is located on Kedawung Street, No.3 Lemahabang. The results of the visit show that Candu Koffie initially did not accurately calculate production costs, and certain costs were also not included in the cost of goods sold. Candu Koffie considers production costs such as raw material costs, labor costs, and overhead costs. However, they do not include costs such as electricity, water, and other discount costs in determining the selling price of their products and sales. This visit provides valuable insights, especially in the food and beverage industry, to develop effective pricing strategies. With a better understanding of the factors that influence appropriate pricing.